The relevance of green branding on competitive strategies in service firms - Morka, Ogor Tessy; Aliku, Ifeanyi Harold (International research journal of management, IT and social sciences, 2022)
The study evaluated qualitatively the relevance of green branding in service firms. Drawing the manufacturing industry perspective. Two objectives were drawn for this bordering on environmental actors and green innovation as it affects competitive advantage, The extant literature revealed a strong impact of these predator variables on competitive advantage in service industry management. The findings was that the performance of green innovation, product and process has a positive influence on the performance of the firms, although green innovation process is rarely discussed in the literature, it is very important to highlight the green innovation process, as it is easy to imitate the final product, compared to the process. Recommendations were made on the need to continue to uphold green innovation and major environmental factors to promote firm performance and profitability.